The effect of histologic grade on neoadjuvant treatment outcomes in esophageal cancer. Issue 3 (16th May 2022) - Pointer, David T.; McDonald, Jordan A.; Naffouje, Samer A.; Mehta, Rutika; Fleming, Jason B.; Fontaine, Jacques P.; Lauwers, Gregory Y.; Frakes, Jessica M.; Hoffe, Sarah E.; Pimiento, Jose M.
Abstract: Background and Objectives: The gold standard for locoregional esophageal cancer (LEC) treatment includes preoperative chemoradiation and surgical resection, with possible perioperative or adjuvant systemic therapy. With few data associating histologic grade and prognosis in LEC patients receiving neoadjuvant chemoradiation followed by resection, we seek to evaluate this association. Methods: Our institutional esophagectomy database between 1999 and 2019 was queried, selecting esophageal adenocarcinoma patients who completed neoadjuvant therapy (NAT), followed by esophagectomy. Propensity‐score matching of low‐ and high‐histologic grade groups was performed to assess survival metrics using initial clinical grade (cG) and final pathologic grade (pG). We performed a multivariable logistic regression to study predictors of pathologic complete response as a secondary objective. Results: A total of 518 patients met the inclusion criteria. Kaplan–Meier analysis of the matched dataset showed no difference in initial or 5‐year recurrence‐free survival or overall survival (OS) between cG1 and cG2 versus cG3 based on original grade. When matched according to pG, cG1–2 had improved median survival parameters compared to cG3, with 5‐year OS for cG1–2 of 45% versus 27% ( p = 0.001). Higher pG, pathologic N stage, and poor response to NAT are predictors of poor survival. Conclusion: Patients with post‐NAT pG1–2 demonstrated improved survival. Integrating histologic grade into postneoadjuvant staging may be warranted.